Designing A Compact 2×2 Dual-Band Mimo Microstrip Antenna for Wireless Monitoring Systems in Oil and Gas Facilities - Aribowo, Didik; Nawawi, Zainuddin; Suprapto, Bhakti Yudho (Testing Center for Oil and Gas LEMIGAS, 2026)
Oil and gas facilities present challenging wireless communication environments due to complex metallic structures and severe multipath propagation, which can degrade the reliability of Industrial Internet of Things (IIoT)–based monitoring systems. To address this issue, this study proposes a compact dual-band 2×2 MIMO microstrip antenna operating at 2.6 GHz and 3.8 GHz for wireless monitoring applications in oil and gas facilities. The antenna is fabricated on a low-cost FR-4 substrate and employs a hexagonal patch geometry, miniaturized using a beveled half-cut technique to shorten the effective current path while maintaining good impedance matching. Furthermore, a multi-bridge ground structure is introduced to reduce mutual coupling between MIMO elements. Antenna performance is evaluated through simulations using Computer Simulation Technology (CST) by analyzing S-parameters, VSWR, gain, and radiation patterns. Simulation results show that the proposed antenna achieves reflection coefficients below −10 dB at both operating bands, inter-element isolation of up to ≤ −20 dB, VSWR values below 1.5, and a peak gain of 1.41 dBi. These results indicate that the proposed compact dual-band MIMO antenna is a promising candidate for reliable wireless monitoring systems in oil and gas facilities.